DIGITAL MARKETING AS A SOLUTION TO THE CHALLENGE OF MSME MARKETING SUCCESS IN THE ERA OF THE COVID-19 PANDEMIC - Anggit Yoebrilianti; Nurhayani (Jurnal Ekonomi, 2022)
This study examines how Digital Marketing is one of the solutions used by MSMEs to survive and grow in the Covid-19 pandemic era. The object of research is 35 thousand MSMEs who have been affected by the pandemic era. The method used in this research is a literature study. The results of this study are that in the era of the epidemic, consumers almost forgot about the brand, so that promotion through digital advertising can remind brand awareness. Digital marketing can expand the marketing reach of MSMEs. And with the massive use of digital marketing, it has been done to increase customer awareness. Maketplace is a form of investment from e-commerce, namely solutions or changes in marketing and sales methods.